2011
DOI: 10.1017/s0031182011000965
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization experiments indicate incomplete reproductive isolating mechanism between Fasciola hepatica and Fasciola gigantica

Abstract: Experiments on hybridization between Fasciola hepatica and Fasciola gigantica were carried out to clarify whether a reproductive isolating mechanism appears between the two Fasciola species. Molecular evidence for hybridization was based on the DNA sequence of the internal transcribed spacer 1 (ITS1) region in nuclear ribosomal DNA, which differs between the species. The results suggested that there were not pre-mating but post-mating isolating mechanisms between the two species. However, viable adults of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…In laboratory experiments, hybridization was proven for different Schistosoma spp. [24-27] and two other trematodes, Fasciola hepatica and Fasciola gigantica [28]. In most of these laboratory studies, hybrids showed reduced survival and impaired fertility already in the F1 or F2 generation.…”
Section: Resultsmentioning
confidence: 99%
“…In laboratory experiments, hybridization was proven for different Schistosoma spp. [24-27] and two other trematodes, Fasciola hepatica and Fasciola gigantica [28]. In most of these laboratory studies, hybrids showed reduced survival and impaired fertility already in the F1 or F2 generation.…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps the aspermic Fasciola specimens described in the literature [53] were infertile hybrids of F. gigantica and F. hepatica (in situations where both species occur in sympatry). Questions that might be addressed directly in relation to Fasciola sp.…”
Section: Discussionmentioning
confidence: 99%
“…According to Amer et al (2011), the identification of fasciolids requires at least ITS2 and mitochondrial cox1 or nad1 sequences. Itagaki et al (2011) suggested that ITS1 sequences, which do not show variation in Europe or Oceania, are nonetheless useful molecular markers for discriminating F. hepatica, F. gigantica, and their hybrids occurring in Asia (Amer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%